The Role of ESG in Driving Firm Profitability: Implications for Stakeholder, Resource-Based View, and Triple Bottom Line Theories in Emerging Markets - Chipimo, Mubanga Lackson; Bwalya, John; Kanyanga, Joseph Katongo (SEISENSE (PRIVATE) LIMITED, 2025)
Purpose- This study examines how Environmental, Social, and Governance (ESG) practices influence firm profitability and extend key strategic theories like the Stakeholder Theory, Resource-Based View (RBV), and the Triple Bottom Line (TBL) within Zambia’s food sector.Design/Methodology- Using a mixed-methods approach, the study analysed panel data from 2014 to 2024 for listed food companies in Zambia. Fixed effects regression with lagged ESG variables was applied to address endogeneity. Qualitative content analysis of corporate sustainability and governance reports complemented the quantitative findings.Findings- The regression model explains 55.6% of the variation in firm profitability, as indicated by the adjusted R². Among the ESG components, governance practices exhibited a statistically significant positive influence on profitability (coefficient = 23.39, p = 0.015). In contrast, environmental initiatives showed a significant short-term negative effect (coefficient = –32.60, p < 0.001), while social factors did not demonstrate a statistically significant impact.Practical Implications- Firms in emerging markets should embed ESG into core strategy, supported by robust governance. Policymakers must strengthen regulatory frameworks to facilitate sustainable business practices. Future studies are encouraged to further investigate ESG dynamics in resource-constrained settings.Originality/Value – This study contributes to ESG literature in emerging markets by integrating theoretical perspectives with empirical evidence, offering nuanced insights into how ESG performance shapes profitability and strategic outcomes.